Green synthesized Fe3O4@CD nanocomposites using Acacia caesia leaves: In vitro biological properties and cytotoxicity assessment - M. Padmaja; P. Shyamala; V. Durga Praveena; G. Tejaswini (Next Nanotechnology)
The aim of the present study is to prepare carbon dots (CDs) from Acacia caesia leaves and use them to synthesize Magnetite@CD (Fe3O4@CD) nanocomposites (NCs). The absorbance spectrum, photoluminescence, and surface functional groups were revealed in the optical and morphological properties analysis, which confirmed the successful formation of Fe3O4@CD NCs. Electron microscopy showed that the NCs had an almost spherical shape, with an average particle diameter of 11.02 nm. A vibrating sample magnetometer (VSM) also confirmed the superparamagnetic behavior of Fe3O4@CD NCs behaved in a superparamagnetic way. This study also observed effective in vitro antioxidant, anti-inflammatory, and cytotoxicity properties, all with low inhibitory concentration 50 (IC50) values. However, neither Candida albicans nor Aspergillus niger showed any potential antifungal activity by both CDs and Fe3O4@CD NCs. The synthesized Fe3O4@CD NCs demonstrate significant potential for biomedical applications due to their superparamagnetic properties and low IC50 values, offering new insights into the design of multifunctional nanocomposites. Tuning the physiochemical properties of nanomaterials can have broad-field scientific applications.